Swimming Training Attenuates Allodynia and Hyperalgesia Induced by Peripheral Nerve Injury in an Adult Male Rat Neuropathic Model: Effects on Irisin and GAD65. Issue 11 (5th January 2018) - Farzad, Babak; Rajabi, Hamid; Gharakhanlou, Reza; Allison, David J; Hayat, Parisa; Jameie, Seyed Behnamedin
Abstract: Objective: The analgesic mechanism of long-lasting exercise on neuropathic pain is not well understood. This study explored the effects of swimming training on neuropathic pain and the expression of irisin, GAD65, and P2X3 after chronic constriction injury (CCI) of the sciatic nerve. Methods: Thirty-five male rats were randomly assigned to one of the following five groups: 1) no CCI or swimming (control); 2) swimming without CCI (SW); 3) swimming with CCI (CCISW); 4) CCI without swimming (CCI); and 5) sham CCI surgery (sham CCI). Behavioral responses to mechanical, cold, and heat stimuli were tested before and after CCI surgery, as well as each week throughout the four weeks of swimming training. The expression of irisin, GAD65, and P2X3 proteins in L4-L6 spinal cord segment, ipsilateral to the nerve injury, were evaluated by western blotting. Results: Mechanical hyperalgesia was alleviated between the second and fourth weeks of training in the CCISW group. In the tactile allodynia and heat hyperalgesia tests, withdrawal thresholds of the CCISW group were significantly higher than the CCI group at the third and fourth week of training ( P  < 0.05), while cold allodynia showed delayed improvement occurring by the fourth week of training. The expression of irisin was lower in the CCISW and SW groups compared with the CCI group at day 33 post-CCI surgery. Moreover, CCI surgery significantly decreased the protein expression of GAD65 in L4-L6 spinal cord segments ( P  = 0.018), whereas swimming training prevented the decline of GAD65 in the CCISW group. Conclusions: Our findings showed that four weeks of swimming training produce beneficial rehabilitative effects on neuropathic pain symptoms. The analgesic effect of swimming training is partially related to the increase of GAD65. The beneficial role of irisin in neuropathic pain will require further investigation.